PELATIHAN PEMANFAATAN LIMBAH PASAR BUAH SEBAGAI PAKAN TERNAK SAPI DI DUSUN BATUPARAS, DESA PADANGSAMBIAN KAJA, KECAMATAN DENPASAR BARAT, DENPASAR - BUDIASA, I K. MANGKU; PUTRI, B. R. T.; SUMADI, I K.; WIBAWA, A. A. PUTRA (Buletin Udayana Mengabdi, 2012)
ABSTRACT This community service was held at Batuparas, village of Padangsambian Kaja, sub district of West Denpasar involving thirteen local farmers. The teams presented (1) about various vegetables and fruits market’s wastes, (2) how to use and solve it, (3) how to give the wastes to the cattle, (4) adding of concentrate to livestock, (5) preventing of disease and health animals knowledge, and (6) discussion and interview. Based on the limited discussion, it could be seen that the participants were very enthusiastic in joining the activity. They used this occasion for making discussion with the concerned team from Udayana University.